Morta Las Vegas : CSI and the problem of the West - Lewis, Nathaniel, 1962-; Tatum, Stephen, 1949- (Postwestern horizons., 2017)
Through all its transformations and reinventions over the past century, "Sin City" has consistently been regarded by artists and cultural critics as expressing in purest form, for better or worse, an aesthetic and social order spawned by neon signs and institutionalized indulgence. In other words, Las Vegas provides a codex with which to confront the problems of the West and to track the people, materials, ideas, and virtual images that constitute postregional space. Morta Las Vegas considers Las Vegas and the problem of regional identity in the American West through a case study of a single episode of the television crime drama CSI: Crime Scene Investigation. Delving deep into the interwoven events of the episode titled "4 x 4," but resisting a linear, logical case-study approach, the authors draw connections between the city--a layered and complex world--and the violent, uncanny mysteries of a crime scene. Morta Las Vegas reveals nuanced issues characterizing the emergence of a postregional West, moving back and forth between a geographical and a procedural site and into a place both in between and beyond Western identity